2008
DOI: 10.6090/jarq.42.267
|View full text |Cite
|
Sign up to set email alerts
|

Regional Consequences of Seawater Intrusion on Rice Productivity and Land Use in Coastal Area of the Mekong River Delta

Abstract: This study investigates rice productivity in the coastal area of the Mekong River Delta, Vietnam focusing on relationships with the influences of seawater intrusion and recent changes in the land use at regional scale. We examined the statistical data on rice production at 30 districts of 4 provinces in the coastal area for the years 2003-2005, together with the average salinity concentration observed at 48 points in canals and rivers during the dry season. As an index of the extent of seawater intrusion to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 10 publications
0
20
0
Order By: Relevance
“…The Mekong river delta (Figure 1c) is the world's third largest delta, and it is formed by a large transboundary river system travelling through China, Myanmar, Lao People's Democratic Republic (Laos) Kingdom of Thailand, Cambodia and Vietnam (Tin et al 2001;Kotera et al 2008;Armitage et al 2015;Givental and Meredith 2016). It is a territory where regional meteorological and hydrological regimes support diverse social and economic activities, as well as a diverse and productive natural environment.…”
Section: Mekongmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mekong river delta (Figure 1c) is the world's third largest delta, and it is formed by a large transboundary river system travelling through China, Myanmar, Lao People's Democratic Republic (Laos) Kingdom of Thailand, Cambodia and Vietnam (Tin et al 2001;Kotera et al 2008;Armitage et al 2015;Givental and Meredith 2016). It is a territory where regional meteorological and hydrological regimes support diverse social and economic activities, as well as a diverse and productive natural environment.…”
Section: Mekongmentioning
confidence: 99%
“…The construction of several large-scale dams, and major channel-bed mining activities (Piman et al 2013), have now been reported as the cause of an imbalance between flow and sediment entrainment conditions (Xue et al 2011), affecting human livelihoods and the ecological equilibrium in the delta. Predictions of exposure to the effects of climate change for the Mekong delta include a rising sea level, rising temperatures, increased variability in rainfall regime and higher frequency of extreme events (Kotera et al 2008;Haruyama and Ito 2009;Nguyen et al 2014). These changes are likely to have strong negative impacts on the production of food and human wellbeing (Nguyen 2011;Berg et al 2012;Berg and Tam 2012;Kotera et al 2014).…”
Section: Mekongmentioning
confidence: 99%
“…Variations in the available water resources and in water quality, which are strongly governed by salinity intrusion during the dry season and flooding during rainy months, are the key factors determining the cultivation calendar and number of crops (i.e. single, double, or triple) in various parts of the delta (Wassmann et al, 2004;Kotera et al, 2008).…”
Section: Study Areamentioning
confidence: 99%
“…However, surface water may contain potentially hazardous chemicals like pesticides [4] and should therefore always be monitored for these substances. In the coastal region (Soc Trang province), surface waters already contain high loads of total salts due to sea water intrusions, with concentrations between 3 and 6 g·L −1 [27], which makes this source unsuitable for drinking. Therefore, groundwater is the main source for piped-water supplies in these regions.…”
Section: Salinitymentioning
confidence: 99%